Therapeutic Potential and Molecular Mechanisms of Echinacoside in Neurodegenerative Diseases - Li, Jin; Yu, Hongni; Yang, Chuan; Ma, Tao; Dai, Yuan (Frontiers in Pharmacology, 2022)
Echinacoside (ECH) is a natural phenylethanoid glycoside (PhG) in Cistanche tubulosa. A large number of studies have shown that ECH has very promising potential in the inhibition of neurodegenerative disease progression. Experimental studies strongly suggest that ECH exhibits a variety of beneficial effects associated with in neuronal function, including protecting mitochondrial function, anti-oxidative stress, anti-inflammatory, anti-endoplasmic reticulum stress (ERS), regulating autophagy and so on. The aim of this paper is to provide an extensive and actual summarization of ECH and its neuroprotective efficacy in prevention and treatment of neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease (PD), amyotrophic lateral sclerosis (ALS), and so on, based on published data from both in vivo and in vitro studies. There is a growing evidence that ECH may serve as an efficacious and safe substance in the future to counteract neurodegenerative disease.